2002
DOI: 10.1095/biolreprod.102.006700
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vascular Endothelial Growth Factor/Vascular Permeability Factor Action Blocks Estrogen-Induced Uterine Edema and Implantation in Rodents1

Abstract: Estrogen induces a rapid increase in microvascular permeability in the rodent uterus, leading to stromal edema and a marked increase in uterine wet weight. This edema is believed to create an environment optimal for the growth and remodeling of the endometrium in preparation for implantation and pregnancy. Increased endometrial microvascular permeability also occurs in conjunction with implantation. Estrogen-induced uterine edema is immediately preceded by an increase in the expression of vascular endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 68 publications
6
81
1
1
Order By: Relevance
“…The link between estrogens and VEGF production has been demonstrated (Cullinan-Bove & Koos 1993, Bausero et al 1998). Rockwell et al (2002) showed that immunoneutralization of VEGF reduced the uterine edema induced by estrogens and blocked implantation. VEGF acts primarily through binding to VEGFR2 (Ferrara et al 2003, Ferrara 2004; however, estrogens also indirectly induce VEGFR2 expression via VEGF production (Hervé et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between estrogens and VEGF production has been demonstrated (Cullinan-Bove & Koos 1993, Bausero et al 1998). Rockwell et al (2002) showed that immunoneutralization of VEGF reduced the uterine edema induced by estrogens and blocked implantation. VEGF acts primarily through binding to VEGFR2 (Ferrara et al 2003, Ferrara 2004; however, estrogens also indirectly induce VEGFR2 expression via VEGF production (Hervé et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, VEGF and VEGFR2 mRNA expressions were elevated in pregnant mares when compared with cyclic mares, likely reflecting conceptus estrogens (CullinanBove & Koos 1993, Bausero et al 1998, Rockwell et al 2002 and the consequent VEGF-induced expression of VEGFR2 (Hervé et al 2006). The expression of VEGFR2 in pregnant mares on day 21 was greater than that on day 14.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine oedema decreased (lower echotexture scores) in the pregnant group after day 26, which may be a result of continued progesterone exposure. Mechanisms involved in the development of uterine oedema have been discussed (Rabbani & Rogers 2001, Rockwell et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…However, the commercial anti-VEGF/VEGFR2 used in such experiments can induce severe side effects (Eremina et al 2008), which rules out its use in the treatment of endometriosis in young and otherwise healthy women. Moreover, such compounds can also affect other important physiologic processes, including early pregnancy, by blocking implantation-related ovarian (Wulff et al 2001, Zimmermann et al 2001a, 2001b, Pauli et al 2005 and uterine angiogenesis (Rockwell et al 2002, Heryanto et al 2003.…”
Section: Introductionmentioning
confidence: 99%